Status of Women Enrolment in the Higher Education in India: Examining Women Enrolment and Participation in Higher Education Institutes in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Women education and empowerment are the indicators of development. Women education ensures the holistic and long development. It includes equitable and increased access to technical and vocational education and training, higher education and research with due attention to quality assurance. This communication has taken a look on women participation through women higher education institutes, women enrolment as compared with population.